Carboximetilglucana extraída da Saccharomyces cerevisiae previne alterações corporais, metabólicas e cardiovasculares induzidas pelo consumo de dieta hipercalórica em ratos - Torres, Rayanne de Araújo (2019)
Obesity is a multifactorial chronic disease characterized by high body fat accumulation and a chronic proinflammatory state associated with other disorders such as glucose intolerance, dyslipidemias, hepatic steatosis, increased production of reactive oxygen species (ROS) and oxidative stress, and high cardiovascular risk, especially endothelial dysfunction, platelet aggregation, and hypertension. Hypercaloric diets have been widely used to induce obesity and metabolic complications in experimental studies, and thus allow the study of new strategies for the treatment of numerous chronic diseases. Thus, carboxymethyl glucan (CMG), a semisynthetic derivative of Saccharomyces cerevisiae β (1 → 3) (1 → 6) glucan, has been of interest for its immunostimulant effects and high antioxidant capacity. Thus, the study evaluated the effects of CMG on metabolic and cardiovascular changes induced by the consumption of hypercaloric diet in rats. The Animal Use Ethics Committee approved all experimental protocols of UFPB (CEUA 074/2017). Wistar rats were divided into three groups, NCT: normal caloric control; HCT: hypercaloric control; H-CMG: hypercaloric + CMG, the first received standard diet and saline solution, and the last two received hypercaloric diet, the last group being supplemented with CMG at a dose of 20 mg/kg/ day for 12 weeks. Weight and food intake data were evaluated throughout the experimental period. Glucose tolerance and systolic blood pressure (SBP) levels were evaluated in the last week and last day of the experiment, respectively. At the end of the study, dietary and morphometric parameters, fasting blood glucose, lipid profile, inflammation, and histology were analyzed, as well as platelet aggregation, oxidative stress, and vascular reactivity levels. Statistical tests were used to verify significant differences between groups (p <0.05). Treatment with CMG reduced the food intake and weight gain of rats, as well as reducing body fat accumulation, decreasing retroperitoneal fat deposits and adiposity index. Liver fat accumulation also decreased after treatment, as evidenced by histological tests and liver weight. There was an improvement in the glycemic and lipemic profile of rats, improving glucose sensitivity and reducing triglyceride, total cholesterol, and atherogenic index levels. Regarding inflammation, there was a significant improvement in the proinflammatory state observed in the animals of the HCT group. The H-CMG group showed a reduction in CRP, IL-12, and monocyte chemotactic protein-1 (MCP-1) levels, and increased IL-10, and histological tests suggested a reduction in tissue inflammation with a decreased infiltration of inflammatory cells. The cardioprotective effect was also evidenced by the antioxidant capacity of the compound, which significantly reduced in situ and platelet ROS levels, improving nitric oxide (NO) bioavailability and acetylcholine-induced vasorelaxation (ACh). Significant differences were not observed in contractile function, as assessed by phenylephrine (FEN) and sodium nitroprusside-induced vasorelaxation (SPL), and SBP did not significantly decrease after CMG consumption. Finally, there was a reduction in platelet aggregation levels stimulated by biological agonists such as ADP (10 μM) and Forbol Ester (PMA, 100 ng / mL), favoring the reduction of cardiovascular risk induced by the hypercaloric diet. The study data provide relevant evidence about the biological potential of CMG to reduce the damage caused by the consumption of high-calorie diet and emerges as a therapeutic strategy for the treatment of obesity-related diseases and cardiometabolic disorders.